Pizza and Taco. 4, Too cool for school - Shaskan, Stephen (New York : Random House, 2022)
Best friends Pizza and Taco are ready to head back to school, but there are lots of other cool kids, like Cheeseburger and B.L.T.
School Library Journal, August 2022
1.6
K-3
GN360L
Keywords: Best friends -- Comic books, strips, etc; Best friends -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Pizza -- Comic books, strips, etc; Pizza -- Juvenile fiction; Tacos -- Comic books, strips, etc; Tacos -- Juvenile fiction; First day of school -- Comic books, strips, etc; First day of school -- Juvenile fiction; Schools -- Comic books, strips, etc; Schools -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Pizza -- Fiction; Tacos -- Fiction; First day of school -- Fiction; Schools -- Fiction; Humorous stories; School comics; Humorous comics; Graphic novels; Comics (Graphic works)